Effect of Different Dietary Energy Sources on Induction of Fatty Liver-Hemorrhagic Syndrome in Laying Hens - Zhang, Jinwei; Chen, Daiwen; Yu, Bing (International Journal of Poultry Science, 2008)
This experiment was conducted to determine the effect of different dietary energy sources on hepatic lipid content and induction of Fatty Liver-Hemorrhagic Syndrome in laying hens. One hundred and fifty Lohmann commercial layers were divided into three groups of fifty birds each. According to a single factorial arrangement, birds were given one of three experimental diets with control(group 1, 2.65Mcal/kg),or high energy diet which was offered with 7% lard (group 2, 3.06Mcal/kg) and offered with 26% cornstarch (group 3, 3.00Mcal/kg). High energy diets decreased feed intake and egg production (p